Imbalanced MMP-3 and MMP-12 serum levels in systemic lupus erythematosus patients with Jaccoud's arthropathy and a distinctive MRI pattern. (6th January 2021) - Piga, Matteo; Congia, Mattia; Balestrieri, Antonella; Angioni, Maria Maddalena; Cangemi, Ignazio; Cau, Riccardo; Chessa, Elisabetta; Floris, Alberto; Figus, Fabiana; Iagnocco, Annamaria; Cauli, Alberto; Saba, Luca
Abstract: Objective: Metalloproteinase (MMP)-3 and MMP-12 are proteolytic enzymes especially implicated in joint inflammation. This study aims to evaluate their association with arthritis features and hand MRI abnormalities in patients with SLE. Methods: Fifty SLE patients, with a mean (s .d .) age of 48.1 (14.6) years were tested for MMP-3 and MMP-12 serum levels, then further classified according to the presence of X-ray erosions and joint deformities. Eighteen RA patients aged 47.9 (11.8) and 14 healthy people aged 46.0 (11.0) were enrolled as control groups. A subgroup of 28 SLE patients underwent a dominant-hand MRI; the detected changes were classified and semi-quantitatively scored as capsular swelling, synovitis, edematous or proliferative tenosynovitis, bone oedema, bone erosions. Statistical analysis was performed using multiple regression models. Results: MMP-3 were significantly higher in patients with Jaccoud's arthropathy (JA) (22.1 ng/ml, P < 0.05) and independently associated with hsCRP serum levels (B-coeff 0.50; r  = 0.30; P < 0.05). MMP-12 serum levels were significantly lower in patients with JA (0.18 ng/ml, P < 0.05) and inversely associated with the prednisone daily dose (B-coeff –0.03; r = −0.44; P < 0.01). Capsular swelling and edematous tenosynovitis, the most prevalent hand MRI changes in patients with JA, associated with higher MMP-3 (B-coeff 0.12; r  = 0.66; P < 0.01 and B-coeff 0.08; r  = 0.59; P < 0.01, respectively) and lower MMP-12 serum levels (B-coeff –7.4; r = −0.50; P < 0.05 and B-coeff –5.2; r = −0.44; P = 0.05, respectively). Conclusion: Imbalanced MMP-3 and MMP-12 serum levels are influenced by inflammation and glucocorticoids in SLE patients and associated with JA and distinctive hand MRI changes.